ANALISIS PENGARUH STRUKTUR MODAL, PROFITABILITAS, KEBIJAKAN DIVIDEN, DAN SIZE TERHADAP NILAI PERUSAHAAN (Studi Kasus pada perusahaan Wholesale dan Retail yang terdaftar di BEI tahun 2008-2012) - Arindita, Galuh; Sampurno, R. Djoko (Diponegoro Journal of Management, 2015)
This study condected to analyze the effest of Capital Structure (Debt to Equity Ratio/DER),  Profitability  (Return  On  Equity/ROE,  Dividend Policy  (Dividend  Payout Ratio/ DPR), Firm Size (SIZE) to the  Pay Book Value (PBV). The data used in this study were obtained from the data published annual financial reports companies listed at Indonesia Stock Exchange from 2008-2012.The selection of the sample using purposive sampling and number of sample used by 20 wholesale and retail trade companies. Variables used in this study are Capital Structure (Debt to Equity Ratio/DER), Profitability (Return On Equity/ROE, Dividend Policy (Dividend Payout Ratio/ DPR), Firm Size (SIZE) as an independent variable; and Pay Book Value (PBV) as an dependent variable. The analysis technique used are multiple linier regression.The result showed that DER and DPR have no significant impact to PBV. ROE and SIZE has positive and significantly impacted to PBV.